2005
DOI: 10.1021/bm049478b
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polyhydroxyalkanoates from Agricultural Waste and Surplus Materials

Abstract: To be competitive with common plastics, the production costs of polyhydroxyalkanoates (PHAs) have to be minimized. Biotechnological polymer production occurs in aerobic processes; therefore, only about 50% of the main carbon sources and even a lower percentage of the precursors used for production of co-polyesters end up in the products wanted. A second cost factor in normally phosphate-limited production processes for PHAs is the costs for complex nitrogen sources. Both cheap carbon sources and cheap nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
138
4
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(154 citation statements)
references
References 9 publications
(14 reference statements)
6
138
4
6
Order By: Relevance
“…A systematic study further showed that increasing the concentration of glycerol in the medium resulted in the synthesis of lower molecularweight PHB due to glycerol end-capping, a finding that is certain to have an important implication when using biodiesel-derived glycerol co-product streams to produce PHA. The actual use of a glycerol-rich biodiesel co-product stream for short chain length PHA production was reported by Koller et al (2005). These investigators showed that an unidentified osmophilic organism could produce PHB-co-poly hydroxyvalerate from the glycerol liquid phase from biodiesel production at a yield of 16.2 g polymer l −1 without the addition of an odd-number fatty acid precursor as typically required in other fermentation systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic study further showed that increasing the concentration of glycerol in the medium resulted in the synthesis of lower molecularweight PHB due to glycerol end-capping, a finding that is certain to have an important implication when using biodiesel-derived glycerol co-product streams to produce PHA. The actual use of a glycerol-rich biodiesel co-product stream for short chain length PHA production was reported by Koller et al (2005). These investigators showed that an unidentified osmophilic organism could produce PHB-co-poly hydroxyvalerate from the glycerol liquid phase from biodiesel production at a yield of 16.2 g polymer l −1 without the addition of an odd-number fatty acid precursor as typically required in other fermentation systems.…”
Section: Discussionmentioning
confidence: 99%
“…Its utilization in biodegradable polymer production will be attractive. The utilization of crude glycerol from biodiesel industry has been reported by several authors (Ashby et al, 2004;Borman and Roth, 1999;Koller et al, 2005;Mothes et al, 2007). However, significant decrease in PHB productivity and yields were reported.…”
Section: Introductionmentioning
confidence: 94%
“…About half of this amount is used directly in liquid form, 30% as powdered cheese-whey, 15% as lactose and its byproducts and the rest as cheese whey-protein concentrates [2]. A total of 40×10 6 tons/ year of whey is produced in the European Union [3]; the annual surplus of whey is 13×10 6 tons, containing about 619,250 tons of lactose. Nowadays this surplus is not utilized for further production of lactose; consequently, whey disposal represents a serious problem from both an economical and an environmental point of view.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was the methanol fraction present in the fed stream which was utilized as primary carbon source while glycerol was not consumed according to their results. Nevertheless, the main body of research conducted on the use of crude glycerol as substrate for PHA production reports the preferable use of glycerol compared to methanol (Ashby et al 2004;Bormann and Roth 1999;Cavalheiro et al 2009;Koller et al 2005;Mothes et al 2007;Zhu et al 2010). According to these studies, it would be likely the case that the glycerol fraction will be used for PHB synthesis instead of methanol.…”
Section: Discussionmentioning
confidence: 99%